THE ROLE OF ORGANISATIONAL KNOWLEDGE IN THE PROCESS OF ORGANISATIONAL DEVELOPMENT IN THE CONDITIONS OF WAR - Haliuk, I. B.; Hamuliak, N. M.; Yezhak, F. F. (The actual problems of regional economy development, 2024)
The article is concerned with defining the role of organisational knowledge in the process of enterprise development and the specifics of formation and dissemination of organisational knowledge in the context of changes. To achieve the goal of the study, the article uses the method of theoretical research, general logical and generalisation methods. The authors examine the theory of organisational knowledge creation, which involves strategic intentions, autonomy of key teams and specialists, "shaking up and creative chaos", redundancy of information, diversity of information, and the theory of organisational knowledge formation proposed by the authors of the spiral dynamics of organisational development. A special emphasis is placed on the specifics of organisational knowledge formation within the framework of these theories, taking into account the conditions of wartime. It is noted that transformational conditions require new approaches to the formation and dissemination of knowledge. The article presents the characteristic features of the formation of organisational knowledge in war conditions, which involves an integrated approach: the scope of knowledge on survival in war conditions and professional knowledge. It is noted that such an approach allows forming knowledge of both professional skills and survival skills. The background of professional knowledge provides the psychological aspect of understanding that life goes on, work must be done. The background of survival knowledge provides psychological reassurance and understanding of employees' concern for them and their families. In the course of the study, the specifics of organisational knowledge in the context of change, namely in the context of martial law in Ukraine, are highlighted. It is determined that in times of war, traditional formats of knowledge creation and dissemination are transformed into new approaches. The situation of war requires the use of approaches that take into account the psychological aspects of information perception. A special feature of the process of forming organisational knowledge in wartime is the emotional component, and this should be taken into account in the process of communication interaction when disseminating knowledge. It has been determined that knowledge creation is a specific activity that requires completely different conditions than the usual routine work within standard processes. In wartime, these processes are complicated by the instability of the environment. New challenges arise for companies to ensure the stability of their operations and to acquire not only basic knowledge, but also the knowledge necessary for survival.